ANALISIS MINAT INVESTASI MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS YPPI REMBANG ANGKATAN 2020-2022 - Aditya, Yoga Chandra; Suryandani, Wulan (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2025)
ABSTRACTInterest in investing must be carefully considered because it will impact financial planning.The purpose of this study is to assess the impact of financial literacy, financial behavior, and minimum investment capital on capital market investment interest among students at YPPI Rembang University's Faculty of Business and Economics. The study included students from YPPI Rembang University's Faculty of Economics and Business. The sampling approach was proportional stratified random sampling, with a sample size of 100 respondents. The data analysis technique employs multiple linear regression analysis with SPPS 24.0 tools. The findings of this study indicate that the financial literacy variable has a positive but small effect on investment interest, whereas the financial behavior factors and minimum investment capital have a strong positive effect. The modified R square value is 0.750, indicating that the three independent variables (financial literacy, financial behavior, and minimum investment capital) can explain 75% of investment interest. Meanwhile, 25% is explained by characteristics outside of this study.Keywords:financial literacy, financial behavior, minimum investment capital, investment interest